Association of HER-2 Expression with Age, Tumour Size, Grade, Differentiation and Lymph Node Deposit in Patients with Breast Cancer (TAJ: Journal of Teachers Association, 2020)
Breast Cancer incidence is increasing, but its mortality has started to decrease. The existence of strong reliable prognostic and predictive factors is of utmost importance to the practicing clinician. Some factors are only prognostic such as age, tumor size, and lymph node status, while others are both prognostic and predictive such as hormone receptors and human epidermal receptor 2 (HER’s-2) status. This study was done to see the association of HER-2 positivity with age, tumour size, grade, differentiation and lymph node deposit in breast cancer patient. A cross-sectional type of descriptive study was conducted among 50 patients. Patient age range is from 22 to 64 years (mean 42.64 ± 10.26 years). Tumour size ranged from 1 to 8 cm (mean 4.39 ± 1.564cm). Well differentiated tumour was 20, moderately differentiated tumour was 18 cases and poorly differentiated was 12 cases. HER-2/neu negative included 35(70%) cases and positive included 15(30%) cases. In this study it was found that the association between age groups and tumour differentiation with HER-2/neu status was statistically significant (p=